KEMAMPUAN PROBLEM POSING PADA MATERI BALOK DITINJAU DARI HASIL BELAJAR SISWA SMP GEMBALA BAIK - Junatra, Dionesius Dicky; Yani, Ahmad; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe ability of problem-posing is very closely related to problem-solving. The problem-posing ability of students has not been satisfactory, so researchers are interested in studying more deeply about the ability of problem posing in terms of student's learning outcomes. This research used a descriptive research method with survey research. Subjects of research were grade IX students of Pontianak Gembala Baik Middle School in the academic year 2017/2018 totaling 33 people who were then divided into three levels according to their learning outcomes, namely high, medium, and low levels. Data collection techniques used in this study were test and documentation techniques. The data analysis technique used in this study is descriptive statistics. Based on the results of research conducted, seven students entered the high learning outcomes group, 19 students entered the medium learning outcomes group, and seven students entered the low learning outcomes group. The ability of students to pose problems is directly proportional to the student's learning outcomes. Students with low learning outcomes tend to make reconstruction categories and uncategorical. Students with medium learning outcomes tend to make problems in the category of reconstruction and reformulation. High-level learning outcome's students tend to make reconstruction and imitation categories.Â Kata kunci: Cuboid, Problem posing, Studentâ€™s Learning Outcomes